INTERNET GAMING DISORDER AMONG INDONESIAN MUSLIM UNDERGRADUATE STUDENTS - Fitriani, Wahidah; Kamarudin, Diyana (Psikis : Jurnal Psikologi Islami, 2023)
Internet Gaming Disorder Scale was originally developed to measure Internet Gaming Disorder (IGD) based on the nine criteria proposed by the Diagnostic and Statistical Manual of Mental Disorders, 5th ed. (DSM-5). Until recently, there is no result of prevalence of internet gaming disorder among Indonesian Muslim undergraduate students. The objective of this study is to investigate the prevalence of Internet Gaming Disorder among Indonesian Muslim undergraduate students and to explore what are the factors that cause and have effects of IGD in Indonesian Muslim undergraduate students. A case study approach was utilized to gain insight into the experience of six Muslim undergraduate students in Batusangkar city. Data was collected through semi-structured interviews, and analyzed through coding, categorization, and identification of key data concepts. The findings indicate that the intensity of several game use can influence the prevalence of internet gaming disorder among Muslim undergraduate students. Disrupted conduct, social withdrawal, aggression and poor academic performance are among the many problems that results from excessive gaming use. This research contributes to ongoing discussions about internet gaming disorder and its impact on students’ both psychological and physical wellbeing or health in the field of Islamic education.